2019
DOI: 10.1186/s12865-019-0326-8
|View full text |Cite
|
Sign up to set email alerts
|

NK cell predicts the severity of acute graft-versus-host disease in patients after allogeneic stem cell transplantation using antithymocyte globulin (ATG) in pretreatment scheme

Abstract: BackgroundGraft-versus-host disease (GVHD) is one of the most complex complications after allogeneic stem cell transplantation. Current standard of grading system is based on clinical symptoms in skin, liver and intestinal. However, it’s difficult to differ GVHD and its extent just by clinical manifestation. Here we retrospectively analyzed cell immune function in patients implemented allogeneic stem cell transplantation in Ningbo first Hospital from Jan 2013 to Jan 2018.Resultsthe data are collected from 51 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
(27 reference statements)
1
10
0
1
Order By: Relevance
“…These 67 RCTs ( Liu and Huang 2010 ; Xue eand Li, 2010 ; Ren et al, 2011 ; Luo et al, 2012 ; Shen, 2012 ; Su et al, 2012 ; Zou et al, 2013 ; Liang et al, 2014 ; Song and Yang 2014 ; Yin, 2014 ; Fan et al, 2015 ; Li, 2015 ; Ma et al, 2015 ; Zhang, 2015 ; Cao and Mei 2016 ; Feng et al, 2016 ; Wang, 2016 ; Wang et al, 2016 ; Wu and Bao 2016 ; Zeng et al, 2016 ; Li Q. et al, 2017 ; Liu F. et al, 2017 ; Li Y. et al, 2017 ; Liu Z. et al, 2017 ; Chen, 2017 ; Chen and Shi., 2017 ; Li, 2017 ; Liu, 2017 ; Ma, 2017 ; Ou and Liu 2017 ; Pen, 2017 ; Qiu et al, 2017 ; Wei et al, 2017 ; Yun et al, 2017 ; Zhang, 2017 ; Yang and Liu 2018a ; Yang et al, 2018b ; Dai, 2018 ; Fan et al, 2018 ; Ge, 2018 ; Li et al, 2018 ; Liu, 2018 ; Luo, 2018 ; Lv et al, 2018 ; Shi, 2018 ; Yang, 2018 ; Zhang et al, 2018 ; Liu Q. et al, 2019 ; Cao et al, 2019 ; Chai et al, 2019 ; Chen et al, 2019 ; Cheng, 2019 ; Liu Y. et al, 2019 ; Deng, 2019 ; Jin et al, 2019 ; Li and Tian 2019 ; Yuan, 2019 ; Zhang, 2019 ; Cao, 2020 ; Huo et al, 2020 ;…”
Section: Resultsunclassified
See 1 more Smart Citation
“…These 67 RCTs ( Liu and Huang 2010 ; Xue eand Li, 2010 ; Ren et al, 2011 ; Luo et al, 2012 ; Shen, 2012 ; Su et al, 2012 ; Zou et al, 2013 ; Liang et al, 2014 ; Song and Yang 2014 ; Yin, 2014 ; Fan et al, 2015 ; Li, 2015 ; Ma et al, 2015 ; Zhang, 2015 ; Cao and Mei 2016 ; Feng et al, 2016 ; Wang, 2016 ; Wang et al, 2016 ; Wu and Bao 2016 ; Zeng et al, 2016 ; Li Q. et al, 2017 ; Liu F. et al, 2017 ; Li Y. et al, 2017 ; Liu Z. et al, 2017 ; Chen, 2017 ; Chen and Shi., 2017 ; Li, 2017 ; Liu, 2017 ; Ma, 2017 ; Ou and Liu 2017 ; Pen, 2017 ; Qiu et al, 2017 ; Wei et al, 2017 ; Yun et al, 2017 ; Zhang, 2017 ; Yang and Liu 2018a ; Yang et al, 2018b ; Dai, 2018 ; Fan et al, 2018 ; Ge, 2018 ; Li et al, 2018 ; Liu, 2018 ; Luo, 2018 ; Lv et al, 2018 ; Shi, 2018 ; Yang, 2018 ; Zhang et al, 2018 ; Liu Q. et al, 2019 ; Cao et al, 2019 ; Chai et al, 2019 ; Chen et al, 2019 ; Cheng, 2019 ; Liu Y. et al, 2019 ; Deng, 2019 ; Jin et al, 2019 ; Li and Tian 2019 ; Yuan, 2019 ; Zhang, 2019 ; Cao, 2020 ; Huo et al, 2020 ;…”
Section: Resultsunclassified
“…Of the 67 included trials, 16 studies ( Liu and Huang 2010 ; Shen, 2012 ; Wang, 2016 ; Li Q. et al, 2017 ; Li Y. et al, 2017 ; Chen and Shi, 2017 ; Wei et al, 2017 ; Zhang, 2017 ; Yang ad Liu 2018a ; Ge, 2018 ; Li et al, 2018 ; Liu, 2018 ; Lv et al, 2018 ; Zhang et al, 2018 ; Li and Tian, 2019 ; Zhuang and Zhao, 2020 ) reported at least one case of ADRs, 12 studies ( Xue and Li, 2010 ; Su et al, 2012 ; Song and yang, 2014 ; Cao and Mei, 2016 ; Wu and Bao, 2016 ; Luo, 2018 ; Cao et al, 2019 ; Cheng, 2019 ; Zhang, 2019 ; Cao, 2020 ; Jiang et al, 2020 ; Kang et al, 2020 ) reported no ADRs/ADEs during the study, and 39 RCTs did not mention the information of ADRs/ADEs.…”
Section: Resultsmentioning
confidence: 99%
“…43,44 Though NK cell reconstitution after ATG seems to be more rapid than without the use of ATG, studies concerning NK cell function in this setting are scarce and conflicting. 37,45,46 of grade I-II aGvHD of 54%, grade III-IV aGvHD of 4% and without development of cGvHD. One patient developed severe acute GvHD but received stem cells from an older female donor, known to be associated with highest incidence of aGvHD in haploSCT.…”
Section: Revival Of the Haploidentical Transplantation: The T Cell mentioning
confidence: 99%
“…Moreover, in vivo and in vitro studies show that NK cells are also sensitive to ATG, and NK cell numbers drop dramatically after ATG administration 43,44 . Though NK cell reconstitution after ATG seems to be more rapid than without the use of ATG, studies concerning NK cell function in this setting are scarce and conflicting 37,45,46 . Differences in the effect of KIR‐LM after PTCy between the different studies might be due to differences in the conditioning regimen and stem cell source, resulting in different numbers of alloreactive T cells present in the graft.…”
Section: Nkcell Alloreactivity In the Post‐transplant Cyclophosphamidmentioning
confidence: 99%
“…Natural killer (NK) cells are the first lymphocytes reaching the standard numbers within the first few weeks post-transplantation [2], and, therefore, they play a key role in hematopoiesis during the first months after HSCT. NK cells are recognized as crucial cells for early relapse control, and recent data have demonstrated that NK cells also affect GVHD development [3][4][5]. The exact role of NK cells and crucial parameters, which could help us to improve the outcome of HSCT, are currently broadly investigated.…”
Section: Introductionmentioning
confidence: 99%